Electronic Effects Of Word Of Mouth And Perceived Value On Blood Donor Intention: Theory Of Planned Behavior - Tiny Rahayu; Asep Hermawan; Ayu Ekasari (CV. AFDIFAL MAJU BERKAH, 2023)
The research aims to find out whether electronic word of mouth (E-WoM) and perceived value can be a starting factor in an effort to increase blood donor intention using the expansion of the Theory of Planned Behaviour (TPB) to attract potential onors, especially in the West Java region. The data was collected using a questionnaire shared online with social media users who knew that the Indonesian Red Cross (PMI) was an altruistic agency dealing with blood donors. Data was processed using the structural equation modelling (SEM) approach with the partial least squares method (PLS). Using the help of SmartPLS software, the research found that electronic word of mouth, emotional value, altruistic value, and functional value significantly influenced attitude and succeeded in becoming a starting factor in efforts to enhance blood donor intention. The research also revealed that social value does not support the formation of attitudes that mean people donate blood not for social recognition. The findings provide managerial implications to altruistic institutions in developing appropriate promotion strategies for recruiting potential donors based on the findings, theoretically contribute to the development of TPB theory, and are expected to be a reference for future research related to blood donor intention.